2015
DOI: 10.1002/advs.201500112
|View full text |Cite
|
Sign up to set email alerts
|

Multimetallic Mesoporous Spheres Through Surfactant‐Directed Synthesis

Abstract: Multimetallic mesoporous spheres are successfully synthesized with ultra‐large mesopores with the assistance of nonionic triblock copolymer (F127) as a structural directing agent. The kinetically controlled reduction rate of metal species and the concentration of F127 are critical to the formation of the large mesopores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 59 publications
3
113
0
Order By: Relevance
“…Indeed, without the addition of Pt precursor the reaction did not turn black, indicating that Cu 2+ species cannot be reduced by AA under these conditions (Figure S3 c, Supporting Information). Previous studies revealed that hydrochloric acid (HCl) can also affect the rate of the reaction by decreasing the reduction capacity of AA (Figure S4, Supporting Information) . Synthesizing the nanoparticles without PEO‐ b ‐PMMA resulted in large (diameter ≈500 nm) nonporous PtCu nanoparticles, further confirming that PEO‐ b ‐PMMA serves as the pore‐directing agent (Figure S5, Supporting Information).…”
Section: Resultssupporting
confidence: 52%
“…Indeed, without the addition of Pt precursor the reaction did not turn black, indicating that Cu 2+ species cannot be reduced by AA under these conditions (Figure S3 c, Supporting Information). Previous studies revealed that hydrochloric acid (HCl) can also affect the rate of the reaction by decreasing the reduction capacity of AA (Figure S4, Supporting Information) . Synthesizing the nanoparticles without PEO‐ b ‐PMMA resulted in large (diameter ≈500 nm) nonporous PtCu nanoparticles, further confirming that PEO‐ b ‐PMMA serves as the pore‐directing agent (Figure S5, Supporting Information).…”
Section: Resultssupporting
confidence: 52%
“…If F127 is replaced with other surfactants (e.g., PVP and Brij 58), mesoporous nanostructures cannot be obtained (Figure S4 in the Supporting Information). These results suggest that F127 serves as both a protecting agent for the prevention of particle aggregation and as a structure‐directing agent for directing the formation of the mesoporous structure …”
Section: Resultsmentioning
confidence: 99%
“…Unique properties, such as a high surface area and the presence of multifunctional active sites, offer significant advantages for promising applications, including catalysts or catalysis support of various reactions, adsorption, separation of large molecules, sensors, and fuel cells . Among various types of mesoporous materials, mesoporous metals with high electroconductivity are promising materials to be implemented in electrochemical applications …”
Section: Introductionmentioning
confidence: 99%